2023
DOI: 10.1242/dev.200885
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of gastrulation morphologies

Abstract: During gastrulation, early embryos specify and reorganise the topology of their germ layers. Surprisingly, this fundamental and early process does not appear to be rigidly constrained by evolutionary pressures; instead, the morphology of gastrulation is highly variable throughout the animal kingdom. Recent experimental results demonstrate that it is possible to generate different alternative gastrulation modes in single organisms, such as in early cnidarian, arthropod and vertebrate embryos. Here, we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…We highlight that our biophysical model is sufficient to explain both the wild-type and manipulated gastrulation flows in the chick embryo, which show remarkable similarities to the gastrulation patterns naturally observed in other species. Whether our framework can explain (at least partially) the gastrulation flows in different vertebrates is a separate biological question that requires additional work ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight that our biophysical model is sufficient to explain both the wild-type and manipulated gastrulation flows in the chick embryo, which show remarkable similarities to the gastrulation patterns naturally observed in other species. Whether our framework can explain (at least partially) the gastrulation flows in different vertebrates is a separate biological question that requires additional work ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the recently published paper ( 4 ), we used drugs to modulate the ability for active cell ingression and the initial extent of the prospective mesendoderm and showed that the resulting gastrulation flows mirror those naturally observed in reptiles, amphibians, and fish in a single organism, the chick embryo, consistent with our model predictions. Additional or alternative driving forces may be at play in these other species ( 45 ). For example, studies of amphibian gastrulation in Xenopus have suggested that convergent thickening serves as an additional driving force during blastopore closure ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). Mesendoderm specification is required for large-scale cell flows associated with later stage ingression and intercalation at the PS during gastrulation (27, 50). Here, we have described the distinctive set of cell flows that precede gastrulation in the chick embryo, and the relationship between early and late cell flow has yet to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrulation is a process by which cells become internalized to form inter alia a gastric cavity that the animal uses for food digestion, and thus gastrulation is primarily the origin of the endoderm that significantly contributes to the through-gut. However, in many groups of bilaterian animals, formation of endoderm and mesoderm goes hand in hand [ 2 ]. The mode of gastrulation can vary between invagination and epiboly (the ingrowing of part of the blastula cell sheet that directly leads to the formation of an outer (ectodermal) and inner (endodermal or endodermal/mesodermal) cell sheet), delamination (directional cell division of the blastula epithelium), and immigration (immigration of cells from one pole ( polar immigration ) or the complete surface of the blastula epithelium) (reviewed in Budd and Jensen [ 2 4 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, in many groups of bilaterian animals, formation of endoderm and mesoderm goes hand in hand [ 2 ]. The mode of gastrulation can vary between invagination and epiboly (the ingrowing of part of the blastula cell sheet that directly leads to the formation of an outer (ectodermal) and inner (endodermal or endodermal/mesodermal) cell sheet), delamination (directional cell division of the blastula epithelium), and immigration (immigration of cells from one pole ( polar immigration ) or the complete surface of the blastula epithelium) (reviewed in Budd and Jensen [ 2 4 ]). The place of organized cell immigration (as seen in invagination , epiboly and polar immigration ) is called the blastopore, a structure that is thus crucial for the formation of mesoderm and endoderm.…”
Section: Introductionmentioning
confidence: 99%